Antecedents of Employee Intention to Stay: A Study of Employees in Zimbabwean SMEs - Elizabeth Chinomona (Journal of Economics and Behavioral Studies, 2017)
Most research conducted on the influence of employee perception of equity (EPE), organisational citizenship behaviour (OCB), organisational commitment (OC) and turnover intention (ITS) has been on large organisations and little attention has been paid to SMEs. Studies on EPE and OCB have not filtered down to SMEs in developing countries. The primary objective of the study is to investigate the influence of OCB, EPE and OC on ITS in Zimbabwe’s SME sector. It also sought to ascertain the kind of relationships between OCB and OC, EPE with OC, OCB with ITS, EPE with ITS and finally OC with ITS. Structured questionnaires were distributed to SMEs in five major cities. A quantitative method using Smart PLS was employed to test the relationships among the three hypotheses. The results showed that there is a positive relationship between the three proposed hypotheses. Based on the findings, recommendations will be made to both the government policy makers and SME owners. The proposed study is expected to have practical and theoretical implications to both the policy makers in the government and the owners of small businesses in Zimbabwe. In addition, it will provide added insights and new knowledge to the existing body of literature on human resource management, hitherto not studied extensively in developing countries of Southern Africa and Zimbabwe in particular.